Leisure-Time Exercise improves the Well-being of Arab Undergraduate Students - Kashef Zayed; Ghada Al-Khasawneh; Ehab Omara; Ali Al Shamli; Mahmoud Azab; Ahmad Al Haramleh; Asma Al - Attiyah; Nasser Al Rawahi; Mohammed Hassan (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to evaluate leisure-time exercise and mental well-being of undergraduate Arab students. To achieve these goals, a self-reported exercise scale and Warwick-Edinburgh Mental Well-being Scale (W-EMWBS) were administered on a sample of 703 undergraduate Arab students registered in universities in four Arab countries (318 males, and 385 females; m age = 19.97 ± 1.86)  Descriptive statistics showed that the participants had good levels of mental well-being and that only 26% of them regularly engage in sports activities according to the global recommended health standards, while 39% of them do not practice sports at all. The results revealed that participants who used to engage in different levels of exercise and physical activities during their leisure times have better levels of mental well-being compared to their physically inactive counterparts (p =.000). The study concluded that practicing sports in leisure time, even at limited rates, is associated with a high level of mental health.